2017
DOI: 10.1016/j.celrep.2017.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-Biased Stem Cells Maintain Estrogen-Receptor-Positive and -Negative Mouse Mammary Luminal Lineages

Abstract: SUMMARY Delineating the mammary differentiation hierarchy is important for studying mammary gland development and tumorigenesis. Mammary luminal cells are considered a major origin of human breast cancers. However, how ER+ and ER− luminal cells are developed and maintained remains poorly understood. The prevailing model suggests that a common stem/progenitor cell generate both cell types. Through genetic lineage tracing in mice, we find that SOX9-expressing cells specifically contribute to the development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 38 publications
12
80
0
Order By: Relevance
“…Whether SOX9 continues to mark acinar progenitors and control cell fate in the SG remains to be investigated. In the pancreas SOX9+ cells become lineage restricted over time, contributing solely to the ductal lineage shortly after birth (Kopp et al , 2011), SOX9+ cells in the postnatal mammary gland give rise to estrogen receptor (ER)-negative luminal and basal cells (Malhotra et al , 2014; Wang et al , 2017) and in the hair follicle become restricted to the early bulge progeny of the outer root sheath (ORS) during the tissue growth phase known as anagen (Kadaja et al , 2014). …”
Section: Salivary Gland Developmentmentioning
confidence: 99%
“…Whether SOX9 continues to mark acinar progenitors and control cell fate in the SG remains to be investigated. In the pancreas SOX9+ cells become lineage restricted over time, contributing solely to the ductal lineage shortly after birth (Kopp et al , 2011), SOX9+ cells in the postnatal mammary gland give rise to estrogen receptor (ER)-negative luminal and basal cells (Malhotra et al , 2014; Wang et al , 2017) and in the hair follicle become restricted to the early bulge progeny of the outer root sheath (ORS) during the tissue growth phase known as anagen (Kadaja et al , 2014). …”
Section: Salivary Gland Developmentmentioning
confidence: 99%
“…Lineage-tracing of the luminal cell population has revealed that ER + progeny are restricted to the ER + lineage and, likewise, ER− progeny are restricted to the ER− lineage during pregnancy, lactation and involution 1517 . Furthermore, Wap-Cre, which is active only during pregnancy in the ER − alveolar cells, marked only ER − labeled cells after two pregnancies 18 .…”
Section: Mammary Epithelial Cells Have Limited Plasticity In Vivomentioning
confidence: 99%
“…These studies, together with select lineage tracing reports, document the presence of a bi‐potent basal population (Rios et al , ; Wang et al , ). However, other lineage tracing studies challenge this classical view, proposing instead that the combined action of unipotent basal and luminal progenitors maintains the mammary gland (Van Keymeulen et al , ; Giraddi et al , ; Wuidart et al , ; Wang et al , ). Despite ongoing discussion in this area, a considerable body of work supports specific mammary populations as the candidate cells‐of‐origin for breast cancer subtypes.…”
Section: Introductionmentioning
confidence: 99%